2021
DOI: 10.1002/adma.202105697
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Piezo‐Electrocatalytic Sensing of Ascorbic Acid with Nanostructured Wurtzite Zinc Oxide

Abstract: plays a vital role in biological metabolisms, for example, the digestion of amino acids, as well as the synthesis of adrenalin, certain hormones, and neurotransmitters. [2] AA has also been commonly used for the prevention and treatment of scurvy, [3] cancer, [4] common cold, [5] and AIDS, [6] etc. The design and implementation of cost-effective, high-performance electrochemical sensors for the rapid and accurate quantification of AA concentration in foods or biological fluids are important for many societal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…This sensor is highly sensitive (Figure 22c) and synthesized at low temperatures, and is expected to be manufactured cost-effectively, scalable, and incorporated directly into wearable electrocatalytic devices in the future. [88] In addition, researchers have made brilliant use of piezoelectric technology to increase the specific surface area and sensitivity of sensors for toxic gas detection. [24] For example, Zhang et al designed a room-temperature ammonia (NH 3 ) sensor based on Au-MoSe 2 composite, which demonstrated significantly enhanced catalytic activity of the reaction (Figure 22d) and sensitive response to NH 3 gas based on the piezoelectric effect.…”
Section: Biosensingmentioning
confidence: 99%
“…This sensor is highly sensitive (Figure 22c) and synthesized at low temperatures, and is expected to be manufactured cost-effectively, scalable, and incorporated directly into wearable electrocatalytic devices in the future. [88] In addition, researchers have made brilliant use of piezoelectric technology to increase the specific surface area and sensitivity of sensors for toxic gas detection. [24] For example, Zhang et al designed a room-temperature ammonia (NH 3 ) sensor based on Au-MoSe 2 composite, which demonstrated significantly enhanced catalytic activity of the reaction (Figure 22d) and sensitive response to NH 3 gas based on the piezoelectric effect.…”
Section: Biosensingmentioning
confidence: 99%
“…Trace metals, such as iron, copper, and zinc, are essential for life activities ( Liu et al, 2021 ; Dou et al, 2022 ; Yang et al, 2022 ). It is important that the content of these metals in cells be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…14f). Recently, Liu et al demonstrated a piezo-electrocatalytic sensor based on the charge transfer between the strained ZnO nanostructures and ascorbic acid, 559 promising for monitoring ascorbic acid in sweat, tears, and saliva. Another application of this technology can be envisioned using ascorbate acid oxidase and alcohol oxidase to modify ZnO nanowires; these device variations can be used to mimic taste buds and achieve an artificial gustatory system, 560 which could further extend the application of PENGs to the field of chemical sensing.…”
Section: Pengs For Sweat Sensingmentioning
confidence: 99%